2016
DOI: 10.1103/physreve.94.043104
|View full text |Cite
|
Sign up to set email alerts
|

Extreme dissipation event due to plume collision in a turbulent convection cell

Abstract: An extreme dissipation event in the bulk of a closed three-dimensional turbulent convection cell is found to be correlated with a strong reduction of the large-scale circulation flow in the system that happens at the same time as a plume emission event from the bottom plate. The reduction in the large-scale circulation opens the possibility for a nearly frontal collision of down-and upwelling plumes and the generation of a high-amplitude thermal dissipation layer in the bulk. This collision is locally connecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Zürner et al (2019) found f OS /f κ = (0.010±) × Ra 0.40±0.02 at Pr = 0.029. The direct numerical simulation by Schumacher & Scheel (2016) at Pr = 0.021 results in a scaling f OS /f κ = (0.08±) × Ra 0.42±0.02 . Another scaling law, f OS /f κ = (0.027±) × Ra 0.419±0.006 , is given by Vogt et al (2018a).…”
Section: Dominant Oscillation Frequenciesmentioning
confidence: 95%
“…Zürner et al (2019) found f OS /f κ = (0.010±) × Ra 0.40±0.02 at Pr = 0.029. The direct numerical simulation by Schumacher & Scheel (2016) at Pr = 0.021 results in a scaling f OS /f κ = (0.08±) × Ra 0.42±0.02 . Another scaling law, f OS /f κ = (0.027±) × Ra 0.419±0.006 , is given by Vogt et al (2018a).…”
Section: Dominant Oscillation Frequenciesmentioning
confidence: 95%
“…This is motivated by a recent DNS study where the higher inertia of fluid turbulence in low-Prandtl-number fluids is found to be largely caused by the injection of turbulent kinetic energy at a larger scale due to the coarser thermal plumes comprising the LSC (Schumacher, Götzfried & Scheel 2015). A reverse influence of the small-scale turbulence on the large-scale flow is, however, also possible as extreme dissipation events may trigger LSC reorientations (Schumacher & Scheel 2016). We investigate the turbulent character of the flow from direct determination of the Reynolds number dependence in the cell centre using UDV.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we test these theoretical ideas for Rayleigh-Bénard convection (RBC). The mechanisms of production of turbulent kinetic energy in this flow are connected to life cycles of characteristic coherent structures of the thermal boundary layers [13][14][15][16][17], so the details are bound to be more complex than in homogeneous and isotropic turbulence. In particular, we will study here the scaling of moments of the kinetic energy dissipation rate with respect to Reynolds number.…”
Section: Introductionmentioning
confidence: 99%